Hearing Loss: Stigma Consciousness, Quality of Life and Social Identity. (2019) - Privado, Jesús; Carrasco, Luis; Durán, Rocío
Abstract: In the present research, three tests, Pinel's Stigma Consciousness (1999); Quality of Life by Ruiz and Baca (1993); and the Social Identity by Cameron (2004), were adapted and validated by hearing loss of different ages, educational levels, marital status and occupation in order to make the sample more representative. The content validity was established using a group of experts formed by disabled people and technicians in disability with the purpose of adapting the items of the different tests. The reliability of the three tests was adequate with values higher than .70. The Stigma Consciousness test presented a unifactorial structure, that of Quality of Life with four factors (General Satisfaction, Free Time, Physical and Psychological Well-being and Social Support) and Social Identity with three factors (Centrality, Ingroup Ties and Ingroup Affect). Goodness-of-fit tests showed adequate values. We also analyzed the convergent and discriminant validity of the scale in order to see which tests presented major and minor associations and the criterion validity relating the scales to the level of studies, the percentage of disability and the work place of the evaluated ones. Finally, we analyzed the similarities between our results and those obtained in the original tests.